The Effect of the Use of Audio Visual Media on Student Learning Interest in the Concept of the Pythagorean Theorem - Agnes Lugfi Wulandari mtk; Grace Netty Mainolo; Subhanudin Subhanudin; A Rasul (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine whether there is an effect of using audio visual media on student interest in the subject matter of the Pythagorean Theorem in Class VIII of Timika Adventist Junior High School and how the effect is. The population in this study were all students of class VIII SMP Advent Timika with a total of 124 students. The results of the t-test statistic test using the Independent Sample Test technique to test the hypothesis "Is there any effect of using audio visual media on student interest in the subject matter of the Pythagorean Theorem for Class VIII of Timika Adventist Middle School." The test results show that the tcount value of audio-visual media is 2.327 and the tcount value of student learning interest is 3.327, with a Sig value of 0.000. This shows that the tcount value is greater than the ttable value of 1.671 while the Sig value is smaller than 0.05. Thus Ha is accepted and Ho is rejected, meaning there is a significant influence of the use of audio visual learning media on students' interest in learning the main material of the pythagorean theorem class VIII Timika Adventist Middle School.